The association of maternal vitamin D status with infant birth outcomes, postnatal growth and adiposity in the first 2 years of life in a multi-ethnic Asian population: the Growing Up in Singapore Towards healthy Outcomes (GUSTO) cohort study. Issue 4 (24th June 2016) - Ong, Yi Lin; Quah, Phaik Ling; Tint, Mya Thway; Aris, Izzuddin M.; Chen, Ling Wei; van Dam, Rob M.; Heppe, Denise; Saw, Seang-Mei; Godfrey, Keith M.; Gluckman, Peter D.; Chong, Yap Seng; Yap, Fabian; et al.
Abstract: Maternal vitamin D status during pregnancy has been associated with infant birth and postnatal growth outcomes, but reported findings have been inconsistent, especially in relation to postnatal growth and adiposity outcomes. In a mother–offspring cohort in Singapore, maternal plasma vitamin D was measured between 26 and 28 weeks of gestation, and anthropometric measurements were obtained from singleton offspring during the first 2 years of life with 3-month follow-up intervals to examine birth, growth and adiposity outcomes. Associations were analysed using multivariable linear regression. Of a total of 910 mothers, 13·2 % were vitamin D deficient (<50 nmol/l) and 26·5 % were insufficient (50–75 nmol/l). After adjustment for potential confounders and multiple testing, no statistically significant associations were observed between maternal vitamin D status and any of the birth outcomes – small for gestational age (OR 1·00; 95 % CI 0·56, 1·79) and pre-term birth (OR 1·16; 95 % CI 0·64, 2·11) – growth outcomes – weight-for-age z -scores, length-for-age z -scores, circumferences of the head, abdomen and mid-arm at birth or postnatally – and adiposity outcomes – BMI, and skinfold thickness (triceps, biceps and subscapular) at birth or postnatally. Maternal vitamin D status in pregnancy did not influence infant birth outcomes, postnatal growth and adiposity outcomes in this cohort, perhaps due to the low prevalence (1·6 % of the cohort) of severe maternal vitamin D deficiency (defined as of <30·0 nmol/l) in our population.